Does nutritional status affect treatment tolerability, chemotherapy response and survival in metastatic gastric cancer patients? Results of a prospective multicenter study in Turkey. (January 2022) - Karabulut, Senem; Dogan, Izzet; Usul Afsar, Cigdem; Karabulut, Mehmet; Ak, Naziye; Duran, Ali; Tastekin, Didem
Background: The possible impact of malnutrition on the efficacy and tolerability of modern chemotherapy for metastatic gastic adenocarcinoma (mGC) patients is unclear. With this study, we aimed to represent the possible impact of malnutrition on the efficacy and tolerability of chemotherapy, and also on the overall survival of mGC patients. Methods: In this prospective multicenter study, we collected demographic, oncological and nutritional data of our mGC patients. The nutritional status of patients were assessed with the Nutritional Risk Index (NRI), Body Mass Index (BMI) and weight loss percentage within 21-day period, between the chemotherapy cycles. All of these parameters along with toxicity assessment were evaluated after each courses of chemotherapy in order to determine inter-treatment weight loss. NRIs were calculated with a formula as follows; [1.519 × serum albumin level(g/L) + 41.7 × current weight/basic weight]. Patients were classified as having 'no malnutrition' (NRI > 97.5), 'moderate malnutrition' (97.5 ≥ NRI ≥ 83.5) or 'severe malnutrition' (NRI < 83.5). Drug-induced toxicities and treatment responses were evaluated via National Cancer Institute CTCAE version 4.0 and RECIST Criteria 1.1, respectively. Results: One hundred and sixteen mGC patients were enrolled into the study. Median age was 60 years with range 32–83. Primary location of the tumor was antrum in 40% of the patients and of which 24% had undergone primary tumor resection. Ninety-eight percent of the patients had WHO performance status 0 or 1. Malnutrition was diagnosed in 67% of the patients and was severe in 31% of them. All patients received chemotherapy as first-line setting. Severe malnutrition was not associated with chemotherapy responses (p = 0.57). Moderate/severe malnutrition was associated with more cytopenia, nausea/vomiting, diarrhea, neuropathy, (p < 0.05 for all parameters). Moderate/severe malnutrition is associated with worser non-hematological toxicities (p = 0.038). Forty-one percent of patients died during the follow up period (Median: 138 days, range: 21–378). Malnutritional level was associated with significantly reduced overall survival. Severe malnutrition was associated with shorter median overall survival (74 days (95% CI, 20.7–111.0) vs. 237 (95% CI, 148.4-325.6) in none/moderate groups, p = 0.007). Conclusions: In mGC patients, moderate/severe malnutrition is associated with worse non-hematological toxicities. Severe malnutrition is also associated with reduced overall survival.